Exploring EFL students’ perspectives on vocabulary learning through SkELL: A case study - Khairunnisa Khairunnisa; Sholihatul Hamidah Daulay (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study investigates Indonesian EFL students' perspectives on using Sketch Engine for Language Learning (SkELL) for vocabulary acquisition. Employing a qualitative descriptive case study approach, data were gathered through an online questionnaire completed by twelve undergraduate EFL students and semi-structured interviews with five selected participants. The research aimed to explore students' general attitudes, perceived benefits, and challenges when utilizing SkELL as a corpus-based tool for independent learning. The findings indicate a largely positive preliminary perception, with a significant majority of students finding SkELL easy to navigate and effective in improving contextual understanding of words. Participants reported enhanced independence and motivation in vocabulary learning, and a preference for SkELL over traditional dictionaries due to its provision of real-world sentence examples. While initial challenges related to interface unfamiliarity and feature comprehension were noted, students proactively overcame these through self-directed learning. These experiences fundamentally reshaped their attitudes towards vocabulary acquisition, shifting their focus from rote memorization to a more contextual and evidence-based approach, ultimately fostering enhanced independence and motivation in their language. Students expressed strong recommendations for SkELL to peers and a commitment to continued use of corpus-based tools, highlighting the tool's potential to significantly enhance vocabulary teaching and empower learners with practical, contextually rich language skills for academic and professional communication.